Fuelwood Burning : Utilization Trends for Forest Sustainability in the Cold Desert of Trans Indian Himalaya - Singh, Ashok; Samant, S. S. (Indian Forester, 2025)
In the Indian Himalayan region, heat energy consumption in terms of fuelwood is always given importance. This study has highlighted qualitative and quantitative consumption trends of fuelwood species utilized by people in the Lahaul Valley, a cold desert in the Trans-Indian Himalaya. For each plant species, the average quantum collection, probability of utilization, and Resource Use Index were assessed. The study revealed a diversity of 42 fuelwood species used by the tribal population. Among all the species, maximum Resource Use Index value and preference were recorded for Salix fragilis, followed by Juniperus polycarpos, and Pinus wallichiana. The study also highlighted the available stock of fuelwood species. In recent years, consumption pressure on fuelwood from the forests showed a declining trend, it could be the adoption of sustainable harvesting practices which will save energy by burning fuelwood. Of the total species, the higher dependence on native species (57.14%); near-endemic species (30.95%); and endemic species (2.38%) were recorded, this indicated the importance of these species for conservation. Hence, regular monitoring for extraction trends with changing attitudes of the people is required.